2011
DOI: 10.1016/j.jpowsour.2011.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of MEA degradation under accelerated relative humidity cycling

Abstract: The objective of this work is to identify the failure mode diagnosis protocols for polymer electrolyte membrane (PEM) fuel cells with the use of accelerated testing conditions. The single cells used in this work were constructed using commercial Ion Power ® membrane electrode assemblies (MEAs) and the performance degradation was studied under accelerated dynamic reactant relative humidity (RH) conditions. The influence of RH on cell performance was investigated, and a strong dependence of degradation with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 30 publications
(39 reference statements)
1
29
1
3
Order By: Relevance
“…4. The nearly linear increase in current density with the potential indicates the existence of a short circuit in the MEA [6,9]. By subtracting the contribution of the internal short circuit resistance as explained in [9], the limiting current density of H 2 crossover can be obtained by following equation: …”
Section: Limiting Current Density Of Hydrogen Crossovermentioning
confidence: 99%
See 1 more Smart Citation
“…4. The nearly linear increase in current density with the potential indicates the existence of a short circuit in the MEA [6,9]. By subtracting the contribution of the internal short circuit resistance as explained in [9], the limiting current density of H 2 crossover can be obtained by following equation: …”
Section: Limiting Current Density Of Hydrogen Crossovermentioning
confidence: 99%
“…1 MPa, the open circuit voltage (OCV) decreased significantly from 0.93 to 0.22 V; on the contrary, for (P C ÀP A ) ¼ 0.1 MPa, the OCV remained unchanged. Vengatesan et al [6] and Panha et al [7] developed infra-red (IR) imaging to identify the localization of pinholes on MEA and evidenced that pinholes were formed at the inlet of the dry reactant before being propagated on the MEA surface. Computational fluid dynamics (CFD) simulation [5] showed the formation of a hot spot in the cathode catalyst layer (CL) at the site of the pinhole (Ø ¼ 0.14 mm), with local temperatures 4e5 K higher than in the surrounding area.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the water has to be retained in the ionomer to avoid dehydration and performance loss due to low protonic conductivity. Dehydration also leads to membrane electrode assembly (MEA) degradation due to membrane thinning and pinhole formation [1,2]. On the other hand, the liquid water saturation in the gas diffusion layers (GDLs) must be low enough to sustain the gas transport from the gas channels to the active sites.…”
Section: Introductionmentioning
confidence: 99%
“…17 In order to evaluate the durability and diagnose potential mitigation strategies at reasonable cost and time, accelerated stress testing (AST) is generally applied via aggravating the chemical and mechanical stressors including current density, cell voltage, temperature, and RH fluctuations. 2,4,18 Open circuit voltage (OCV) 13,[18][19][20][21][22][23] and RH cycling [24][25][26][27][28][29][30] AST protocols are generally utilized to exacerbate the rate of chemical and mechanical degradation, respectively. Lai et al 24 performed in-situ humidity cycling tests on different membranes exposed to various RH swings and reported that the time-to-failure was extended as the membranes were subjected to smaller humidity swings.…”
mentioning
confidence: 99%